Changes in Atmospheric Dynamics Over Dansgaard‐Oeschger Climate Oscillations Around 40 ka and Their Impact on Europe - Stadelmaier, Kim H.; Ludwig, Patrick; Pinto, Joaquim G.; Újvári, Gábor (Journal of Geophysical Research: Atmospheres, 2024)
Abstract Dansgaard‐Oeschger (D‐O) climate variability during the last glaciation was first evidenced in ice cores and marine sediments, and is also recorded in various terrestrial paleoclimate archives in Europe. The relative synchronicity across Greenland, the North Atlantic and Europe implies a tight and fast coupling between those regions, most probably effectuated by an atmospheric transmission mechanism. In this study, we investigated the atmospheric changes during Greenland interstadial (GI) and stadial (GS) phases based on regional climate model simulations using two specific periods, GI‐10 and GS‐9 both around 40 ka, as boundary conditions. Our simulations accurately capture the changes in temperature and precipitation as reconstructed by the available proxy data. Moreover, the simulations depict an intensified and southward shifted eddy‐driven jet during the stadial period. Ultimately, this affects the near‐surface circulation toward more southwesterly and cyclonic flow in western Europe during the stadial period, explaining much of the seasonal climate variability recorded by the proxy data, including oxygen isotopes, at the considered proxy sites. Plain Language Summary: The climate during the last ice age varied between colder and warmer periods on timescales ranging from hundreds to thousands of years. This variability was first detected in Greenland ice cores and marine sediment cores of the North Atlantic, as well as in continental geological records in Europe. The variation between the colder and warmer periods occur mostly simultaneously in Greenland and in Europe, which is why the atmosphere is assumed to have an important role in transferring the climate signals. We simulated two different periods of the last ice age, one colder and one warmer around 40,000 years ago, using a regional climate model. The aim was to study how the climate and atmospheric circulation changed during these two periods. We find the eddy‐driven jet over the North Atlantic intensified and shifted southward during the ...